2007
DOI: 10.1161/01.str.0000247934.04848.79
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Surgical Treatment of Atrial Fibrillation

Abstract: Abstract-Atrial fibrillation (AF) is the most common sustained arrhythmia. It is associated with increased risks of death and stroke; most strokes in AF patients are thought to arise from thrombi in the left atrial appendage. Surgical ablation of AF includes excision of the left atrial appendage and is an effective means of treating this arrhythmia, with the classic Maze procedure curing AF in Ͼ90% of patients and virtually eliminating the risk of late stroke. A complex but safe operation, the Maze procedure h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 51 publications
(48 reference statements)
1
27
1
2
Order By: Relevance
“…The Cox-Maze III operation, "cut and sew Maze," or simply Maze procedure is now the gold standard for surgical treatment of atrial fibrillation. The operation may be performed alone or in conjunction with other cardiac surgical procedures, such as mitral valve repair or coronary artery bypass grafting (Gillinov, 2007). In a report of 197 patients who underwent the Maze procedure, the mean rate of freedom from atrial fibrillation was 89% after 10 years of follow-up (Gaynor et al, 2005).…”
Section: The Maze Proceduresmentioning
confidence: 99%
“…The Cox-Maze III operation, "cut and sew Maze," or simply Maze procedure is now the gold standard for surgical treatment of atrial fibrillation. The operation may be performed alone or in conjunction with other cardiac surgical procedures, such as mitral valve repair or coronary artery bypass grafting (Gillinov, 2007). In a report of 197 patients who underwent the Maze procedure, the mean rate of freedom from atrial fibrillation was 89% after 10 years of follow-up (Gaynor et al, 2005).…”
Section: The Maze Proceduresmentioning
confidence: 99%
“…Pharmacologic cardioversion with antiarrhythmic drugs has a low success rate and is often complicated by side effects that negatively affect its risk/benefit ratio (3). Transcatheter and surgical techniques for atrial fibrillation ablation have therefore been developed.…”
Section: See Page 1614mentioning
confidence: 99%
“…Although also adopted for lone atrial fibrillation, the procedure has found its largest application in patients undergoing surgery for other cardiac indications, especially concomitant mitral valve disease, for which its use in combination with mitral valve repair is especially attractive because of the possibility to avoid lifelong anticoagulation. Despite its high success rates in restoring sinus rhythm (Ͼ90% in some series [3]), the Cox Maze III procedure is technically challenging and time consuming, which has led to the introduction of modified techniques aimed at reducing or eliminating the surgical incisions, replacing them with lesions produced by energy sources such as radiofrequency, laser, and cryoablation.…”
Section: See Page 1614mentioning
confidence: 99%
“…In fact, The ACC and AHA have recommended that LAA ligation be performed during the course of valvular surgery, and the Atriclip provides one viable option by which to achieve this goal. [56] In the pivotal trial CT scan follow-up provided proof of absence of LAA thrombus, clip stability, and demonstrated LAA closure in 98% of patients at 6 month follow-up. [55]…”
Section: Introductionmentioning
confidence: 99%